(untitled) (Argos, 2025)
The aim of this paper is to establish in Apuleius’ Metamorphoses the didactic purpose of the inserted tales on bandits Lamachus, Alcimus and Thrasyleon (Apul. Met. IV, 7-22), as exempla, through the analysis of the main features that identify them as exemplary discourses in the context of the Roman culture and the study of formal marks that demonstrate the transmission of doctrinal issues.